2016
DOI: 10.17652/rpot/2016.4.12575
|View full text |Cite
|
Sign up to set email alerts
|

The Saying and the Doing in research on WOP

Abstract: Research on Work and Organizational Psychology -WOP -tends to investigate its phenomena based on what is said, either through surveys or interviews. To what extent do we perceive the complexity of the area's constructs exclusively based on Saying? What explains such predominance? Such questions guided this theoretical essay, which is based on an analysis of the characteristics of the scientific production on some classic themes in organizational behavior. We conclude that the predominance of the comprehension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Further, scales favor generalizability, but they may lack precision and realism. They are subjected to the reliability problems, highlighted by Schwartz and Oyserman (2001), and validity problems, as they are based solely on what the individual says (Mourão et al, 2016). Several constructs, despite being investigated in various contexts, are not necessarily true to reality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, scales favor generalizability, but they may lack precision and realism. They are subjected to the reliability problems, highlighted by Schwartz and Oyserman (2001), and validity problems, as they are based solely on what the individual says (Mourão et al, 2016). Several constructs, despite being investigated in various contexts, are not necessarily true to reality.…”
Section: Discussionmentioning
confidence: 99%
“…Only 12.4% of Brazilian studies reported behavior observation as a method, and most observations are also focused on what the individual says, despite the claim to consider what people do. Thus, they do not incorporate fundamental elements to appropriately understand the phenomenon (Mourão, Bastos, Passos, & Oliveira, 2016). Studies on performance, commitment, and organizational citizenship refer directly to organizational behaviors, but these aspects are investigated almost exclusively by what individuals say, as indicated by Mourão et al (2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The first blended different research traditions and their relevance in the area, such that learning represents a theme with a long tradition in WOP research in Brazil (Loiola & Bastos, 2003), organizational citizenship and justice represent more recent and prominent themes in national and international discussions in WOP (Palazolli, 2000;Rego, 2002;Rego, 2014;Siqueira, 2003;Tamayo et al, 2012), and socialization represents a topic that had a large increase in publications in the last decade (Borges & Albuquerque, 2014). These themes are among the fifteen most investigated in WOP in Brazil, with a total of more than 500 published articles (Mourão, Bastos, & Oliveira, 2016). The theme of learning at work was the most researched, followed by commitment, while the organizational citizenship theme occupied last place.…”
Section: Methodsmentioning
confidence: 99%